Using the Theory of Planned behavior to identify correlates of HPV vaccination uptake among college students attending a rural university in Alabama. Issue 51 (17th December 2021) - Shah, Sayyed Fawad Ali; Ginossar, Tamar; Bentley, Joshua M; Zimet, Gregory; McGrail, J. Patrick
Abstract: Introduction: Humanpapillomavirus (HPV) has infected nearly 80 million people in the U.S., and is associated with most cervical cancer cases. Alabama ranks first in the country for cervical cancer mortality and third for incidence. Although the HPV vaccine can prevent HPV and reduce cancer rates, Alabama is well-below the national average for HPV vaccination. Using the Theory of Planned Behavior (TPB), this Alabama-based study aimed to examine college students' intentions to get the HPV vaccine; to examine the relationship between the relationship between religious beliefs and HPV vaccination uptake status among college students. Methods: Students (n = 257) from a university in rural Alabama completed the survey. Multiple regression analysis, Mann-Whitney U tests, and moderation analysis were used to examine associations among the variables of interest. Findings: Consistent with TPB, results showed that attitudes and subjective norms were significant predictors of intention to get vaccinated. Knowledge that both sexes can experience HPV-related health problems, that HPV can cause genital warts, and that the vaccine protects against HPV were each associated with higher attitude scores. The results indicated that the odds of getting at least one HPV shot were higher for females than for males for non-Caucasians than for Caucasians. Students who were not vaccinated were more likely to report that religion influenced their health beliefs. *Abstract. Conclusion: TPB was helpful in understanding HPV-related intentions. Communication and education efforts are needed to increase understanding of HPV illnesses and HPV vaccination benefits among peers, parents, and other loved ones of students. in the rural areas of Alabama.